Indices d’orfèvrerie et d’élaboration du laiton à Meaux (Seine-et-Marne) au ier s. ap. J.-C. : l’apport des analyses chimiques - Jean-Marc Séguier; Fabien Pilon; David Couturier; Christel Delozanne (Revue Archéologique du Centre de la France)
Several finds made in the context of preventive archaeology show that the metallurgy of iron and copper alloys is well represented in Meaux, capital of a small city in the Roman period. Chemical analysis of recently discovered crucibles attest to the presence of goldworking and brass production. This paper also presents documents related to lead bronze work and a crucible that is probably new.